2009
DOI: 10.1063/1.3187902
|View full text |Cite
|
Sign up to set email alerts
|

Laser thermal annealing effects on single crystal gallium phosphide

Abstract: We have studied the laser thermal annealing ͑LTA͒ effects on single crystal GaP. The samples have been analyzed by means of Raman spectroscopy, glancing incidence x-ray diffraction ͑GIRXD͒, and transmission electron microscopy ͑TEM͒ measurements. After LTA process, the Raman spectra of samples annealed with the highest energy density show a forbidden TO vibrational mode of GaP. This result suggests the formation of crystalline domains with a different orientation in the annealed region regarding the GaP unanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…The important fact is that its intensity increases with annealing energy. This is a similar behavior as for InP layers after PLA, , and indicates the formation of polycrystalline GaMnP film with misoriented domains. The LO peaks of 0.50 and 0.60 J/cm 2 annealed GaMnP exhibit a downward shift to the left side when compared with 0.45 J/cm 2 annealed sample, arising from two effects: (1) the CPLOM appears and shifts the LO peak to lower frequency and (2) the presence of strain introduced by crystalline domain boundaries and defects.…”
Section: Resultssupporting
confidence: 75%
“…The important fact is that its intensity increases with annealing energy. This is a similar behavior as for InP layers after PLA, , and indicates the formation of polycrystalline GaMnP film with misoriented domains. The LO peaks of 0.50 and 0.60 J/cm 2 annealed GaMnP exhibit a downward shift to the left side when compared with 0.45 J/cm 2 annealed sample, arising from two effects: (1) the CPLOM appears and shifts the LO peak to lower frequency and (2) the presence of strain introduced by crystalline domain boundaries and defects.…”
Section: Resultssupporting
confidence: 75%
“…As it can be seen, there are not extended defects in the GaP substrate when the energy density is inside the window defined in the experimental section. This result is clearly different from the one reported in [17], in which a defective polycrystalline layer was produced when the energy density of the PLM process was very high (0.7 J/cm 2 and 1.2 J/cm 2 ). The high quality of the sample shown in the XTEM image of Fig.…”
Section: Resultscontrasting
confidence: 99%
“…In previous studies, we concluded that melting and recrystallization processes under excimer laser radiation are not straightforward for GaP. It seems that for high recrystallization velocities, GaP is not able to regrow following the crystal structure of the underlying nonmelted substrate, and polycrystalline phases appear, though for high energy densities, the crystal quality and the size of the grains increased.…”
Section: Introductionmentioning
confidence: 84%